(untitled) (Kohesi: Jurnal Sains dan Teknologi, 2025)
One of the critical components in the effectiveness of urban logistics is optimizing the delivery routes of goods. As the economic center of the East Java region, Surabaya was chosen because it has a complicated road network with many turns. Therefore, choosing the fastest route becomes a challenge, especially when there is no actual data. This study uses the A-Star algorithm, which is simulation-based, to find the fastest delivery route from one starting point to various destination points. This algorithm was chosen for its ability to find the shortest path based on heuristic values and actual distances. The research method uses three different destinations, with the same starting point of the warehouse at Jl. Sulawesi No.34 in Ngagel, Surabaya. Using interactive maps and graphs, it displays road network data taken from OpenStreetMap. The simulation results show that the A-Star algorithm can find the logical fastest route by avoiding small alleys and using main roads. This research shows that the simulation-based method with the A-Star algorithm can be used well for goods delivery planning.